Effects of Emotional Intelligence on Construction Professionals' Job Performance with Cognitive Styles as Mediator - Alimat Jumoke, Lamina (Universiti Malaysia Sarawak, 2024)
Job performance, encompassing effectiveness, productivity, and job requirement fulfillment, is crucial for career growth and productivity. Conversely, poor performance leads to job dissatisfaction and hinders professional development. In the construction industry, effective job performance is synonymous with project success and directly impacts cost management and timely project completion. Construction professionals play a crucial role in the success or failure of global construction projects, often serving as the yardstick for project success. Effective project delivery hinges on time management, cost control, and thorough planning, which extends beyond technology. While previous studies have predominantly focused on technical issues, human behaviours are the root cause of problems like delays, cost overruns, and subpar project outcomes. Notably, despite their pivotal influence on construction professionals' job performance, emotional intelligence and cognitive styles have received limited attention in existing literature. High levels of emotional intelligence empower construction professionals to communicate effectively, collaborate seamlessly, resolve conflicts, and maintain a positive work environment. In contrast, low emotional intelligence can lead to misunderstandings, poor communication, and internal conflicts, detrimentally impacting project outcomes. Cognitive styles significantly affect how construction professionals approach problem- solving and decision-making. This study investigates the effects of emotional intelligence and the mediator role of cognitive styles on the job v performance of construction professionals registered with Unit Pendaftaran Kontraktor dan Juruperunding (UPKJ) in Sarawak, Malaysia. Employing the cognitive-motivational-relational theory by Richard Lazarus and the four-branch ability model by Mayer and Salovey, the study used survey instruments and a Likert scale questionnaire to gather data from 102 respondents out of 180. Partial Least Square Structural Equation Modeling (PLS-SEM) analysis confirmed that emotional intelligence doesn't significantly impact the job performance of construction professionals in UPKJ Sarawak, Malaysia. This research also underscores the full mediating role of cognitive styles in the relationship between emotional intelligence and job performance among construction professionals. These findings expand the understanding of behavioural factors influencing professionals in the construction industry and serve as a valuable foundation for future research in psychology and construction.